Investigation of immunomodulatory and cytotoxic effects of shed snake skin (Elaphe sauromates) extract - Sinmez, Cagri Caglar; Tüfekçi, Emre; Demir, Büşra Şeniz; Eken, Ahmet; Guneş, Vehbi; Ekici, Seda; Bozkaya, Esra; Aykun, Ali İlteriş (Frontiers in Pharmacology, 2024)
Introduction: Shed snake skin (SSS) is is commonly used empirically in ethnomedicine to treat psoriasis, acne, warts, eczema, scabies, open wounds, hemorrhoids, and glaucoma. Although a few studies exist, SSS extracts' in vitro immunological effects have yet to be well described. Therefore, we aimed to investigate the immunomodulatory effects of SSS extract on murine lymphocytes and T cells. is commonly used empirically in ethnomedicine to treat psoriasis, acne, warts, eczema, scabies, open wounds, hemorrhoids, and glaucoma. Although a few studies exist, SSS extracts' in vitro immunological effects have yet to be well described. Methods: Hexane, methanol, and chloroform extractions were conducted in collected SSS samples. Protein concentrations in the SSS extract were measured. The cytotoxic and anticancer activities were measured using L929 Fibroblast and SK MEL 30 Cell Lines via MTT assay as described in TS EN ISO 10993-5. Immunomodulatory activities of SSS extract on total lymphocytes or enriched CD4+ T cell cultures, their cell-specific pro-inflammatory cytokines (IL-6, IL-1β. IL-12p40, IL-23p19, TNF-α, IL-17A, IFN-γ, IL-10, TGFβ1) levels were measured via FACS ARIA III analysis and related gene expression with Real-Time Quantitative Polymerase Chain Reaction (Rt-qPCR).Results: Hexane, methanol, and chloroform-expressed SSS were tested on SK-MEL-30 cells via MTT and revealed a superior anti-proliferative effect for hexane extract of SSS at low concentrations. SSS treatment of murine lymphocytes augmented Tnf-α and IFN-γ levels produced by CD3+ T cells when lymphocytes were activated with anti-CD3/CD28 or LPS stimulation. This effect required the presence of non-T cells, possibly antigen-presenting cells, and was not observed on purified CD4+ T cells.Additionally, SSS significantly blocked suppressive cytokine Tgfb gene expression (but not Il10) without altering in vitro Treg generation/or expansion.Discussion: This is the first in vitro study investigating SSS's anti-tumor and immunomodulatory effects. Our data provide evidence for SSS's anti-proliferative activity on SK-MEL-30 cells and its pro-inflammatory role on murine lymphocytes, which warrants further investigation of the potential use of SSS extract with in vivo disease models.